2006
DOI: 10.2527/jas.2005-537
|View full text |Cite
|
Sign up to set email alerts
|

Timing of herbage allocation in strip grazing: Effects on grazing pattern and performance of beef heifers1

Abstract: The timing of grazing bouts (GB) determines how cattle allot time to meet their nutritional needs. Net photosynthesis and evapotranspirational losses increase herbage nonstructural carbohydrate and DM concentrations, which may lead to longer and more intense GB at dusk. Hence, linking the grazing pattern, plant phenology, and herbage allocation time emerges as an option to manipulate the GB and nutrient intake. The objectives of this work were to analyze grazing behavior and performance of beef heifers when he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
49
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 26 publications
16
49
0
Order By: Relevance
“…As the extent of herbage depletion increased (P < 0.05), steers increased the feeding station rate, distance walked while eating, and the area covered while grazing, as well as tended (P = 0.09) to take fewer bites per feeding station. These results are consistent with the results presented by Gregorini et al (2006), who found that at the same mass, but different herbage availability and accessibility of wheat pastures, steers changed their foraging dynamic, increasing the eating step rate and reducing residence time per feeding station when accessibility decreased.…”
Section: Resultssupporting
confidence: 95%
See 1 more Smart Citation
“…As the extent of herbage depletion increased (P < 0.05), steers increased the feeding station rate, distance walked while eating, and the area covered while grazing, as well as tended (P = 0.09) to take fewer bites per feeding station. These results are consistent with the results presented by Gregorini et al (2006), who found that at the same mass, but different herbage availability and accessibility of wheat pastures, steers changed their foraging dynamic, increasing the eating step rate and reducing residence time per feeding station when accessibility decreased.…”
Section: Resultssupporting
confidence: 95%
“…The quality of potentially consumed herbage in each grazing scenario was estimated following the methodology used by Gregorini et al (2006). In brief, 9 herbage samples were taken immediately after the grazing sessions mimicking the harvesting movements and bite depth of steers on ungrazed areas next to bitten areas.…”
Section: Behavioral Experimentsmentioning
confidence: 99%
“…Casagrande et al (2011) observed, in a tropical pasture, that less than 30% of cattle were grazing before 08:00 h, but after 09:00 h, 70% of cattle were grazing. On the other hand, Gregorini et al (2006) using Angus heifers ( Bos taurus ) in temperate pastures found longer grazing time at 07:00 h to 11:00 h than at 11:00 h to 13:00 h. These differences in grazing behavior may be due to animal adaptation, where Nellore ( Bos Indicus ) is better able to regulate body temperature in response to heat stress than cattle from a variety of B. taurus (Hansen, 2004) and they may have develop different grazing habits.…”
Section: Discussionmentioning
confidence: 99%
“…These effects may be explained by the greater dry matter (DM) and total nonstructural carbohydrate (TNC) contents of grass grazed in the afternoon. Greater concentrations of TNC have also been observed in annual ryegrass (Gregorini et al 2006), timothy (Morin et al 2012a), tall fescue (Fisher et al 1999) and alfalfa (Morin et al 2012b) harvested in the afternoon compared with the morning. Dumoulin et al (1991) demonstrated that dairy calves supplemented with folic acid had a greater ADG than unsupplemented calves around weaning.…”
mentioning
confidence: 92%
“…Similarly, allocation of a new pasture strip in the afternoon rather than in the morning increased milk yield of dairy cows (Orr et al 2001) and average daily gain (ADG) of beef heifers (Gregorini et al 2006). These effects may be explained by the greater dry matter (DM) and total nonstructural carbohydrate (TNC) contents of grass grazed in the afternoon.…”
mentioning
confidence: 99%